Keterlibatan Indonesia Dalam Penyelesaian Konflik Muslim Moro di Filipina Tahun 1990-2013 - Robby Nugroho; Tri Cahya Utama (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The seeds of the Moro conflict in the Southern Philippines have emerged since the colonialm period. In 1990 the conflict escalated, so that many residents of the Southern Philippines, who are predominantly Muslim, founded resistance organizations. All of this is aimed at fighting or defending his rights against his own government. Therefore, the Moro people are considered by the Philippine government as a threat. The continuity of this conflict resulted in the instability of the Philippines and also affected the Philippines' relations with other countries. Indonesia, as a neighboring country and a region with the Philippines, has helped to resolve the conflict between the Philippine government and the MNLF. This study aims to analyze Indonesia’s involvement in resolving the Southern Philippines conflict. The analysis of this research uses the constructivist concept of identity with qualitative research methods that are descriptive and uses literature studies in data collection. The results of the study indicate that Indonesia's involvement in resolving the Southern Philippines conflict is based on reasons of geographical proximity and the similarity of Islamic religious identity.